Impact of trainee involvement on the outcome of ERCP procedures: results of a prospective multicenter observational trial - Voiosu, Theodor; Boskoski, Ivo; Voiosu, Andrei M.; Benguș, Andreea; Ladic, Agata; Klarin, Ivo; Bove, Vincenzo; Busuioc, Bogdan; Rimbaș, Mihai; Rustemovic, Nadan; Mateescu, Bogdan; Jovanovic, Ivan; Costamagna, Guido (Endoscopy, 2020)
Background Training in advanced endoscopic techniques such as endoscopic retrograde cholangiopancreatography (ERCP) should be driven by key performance measures and standardized competence assessment in order to provide safe and high-quality interventions. We aimed to determine whether the involvement of trainees influences the outcome of the procedure and the incidence of ERCP-related adverse events.Methods This was an international, multicenter, prospective, observational study conducted at six high- and low-volume centers across Europe between October 2016 and October 2018, and included independent operators and their trainees. Standard report forms documenting indication, trainee involvement, technical outcome, and complications over a 30-day follow-up of consecutive ERCP procedures were included in the analysis. Technical success of the procedure and procedure-related adverse events were compared between procedures in the trainee group and the control group using bivariable and multivariable analysis.Results 21 trainees and 16 control endoscopists performed 1843 ERCPs during the study period. Trainee involvement in ERCP procedures did not decrease technical success (92.4 % vs. 93.7 %; P = 0.30) or increase the risk of adverse events (14.7 % vs. 14.6 %; P > 0.99). Conversely, there were significantly more moderate or severe adverse events in the control group compared with the trainee group (6.2 % vs. 3.4 %, P = 0.01). On multivariable analysis, only increased bilirubin levels, time to cannulation, and procedure difficulty level increased the risk of any procedure-related adverse event.Conclusion Trainee involvement in ERCP interventions within a proper teaching setting is safe and does not compromise the success of the procedure.